On the deformation response and cyclic stability of Ni50Ti35Hf15 high temperature shape memory alloy wires. (1st July 2017) - Canadinc, D.; Trehern, W.; Ozcan, H.; Hayrettin, C.; Karakoc, O.; Karaman, I.; Sun, F.; Chaudhry, Z.
Abstract: The processing - phase transformation - deformation response relationship of Ni50 Ti35 Hf15 high temperature shape memory alloy was studied. As the material was hot extruded and further underwent wire drawing, the phase transformation temperatures decreased and the strength levels increased, yet the initial brittle response was replaced by near-perfect superelastic response above the austenite finish temperature. Moreover, the Ni50 Ti35 Hf15 wires exhibited a remarkably stable cyclic actuation response under 300 MPa, as compared to the poor cyclic stability of the hot extruded samples, which is beyond the operating stress levels for known shape memory actuators. Graphical abstract: